Chemical profiles and biological activities of essential oils of Arisaema and Homalomena species (Araceae) – A review - Dam, Sao Mai; Van, Hong Thien (Journal of Phytology, 2022)
In this review, the chemical compositions and bioactivities of the essential oils isolated from Arisaema and Homalomena species, two large genera belonging to the Araceae family, have been reported for the first time. Accordingly, the essential oils isolated from the plants of two genera consisted of some chemical groups, including monoterpene hydrocarbons, oxygenated monoterpenes, sesquiterpene hydrocarbons, and oxygenated sesquiterpenes, etc. In addition, the essential oils and their major compounds isolated from Arisaema and Homalomena plants possessed biological activities, including antimicrobial, insecticidal, nematicidal, antiproliferative, larvicidal and anthelmintic activities. This review mainly provides information on the Arisaema and Homalomena oils which are able to use as a guide for the collection of the species with the best chemical composition and biological activities.